Integral Humanism and the Indian Way: Reconciling Tradition with Modernity - Prof. B. Dharmalingam (The Bioscan, 2025)
Integral Humanism, articulated by Deendayal Upadhyaya in mid-20th century India, offers a unique political and economic philosophy that seeks to transcend the limitations of both Western capitalism and Soviet socialism. Rooted in India's spiritual and cultural heritage, this doctrine presents a holistic vision for human development, social harmony, and national self-reliance. The philosophy emphasizes the integration of material progress with spiritual fulfillment, individual rights with social responsibility, and ethical governance with decentralized development. Integral Humanism advocates for a socio-economic model that prioritizes grassroots development, the preservation of cultural heritage, and ecological sustainability. This article explores the philosophical foundations of Integral Humanism, highlighting its critiques of materialism and collectivism while proposing an alternative model grounded in India's civilizational ethos. Upadhyaya's vision of development, based on the four-fold objectives of life—dharma (righteous duty), artha (economic activity), kama (desire), and moksha (liberation)—serves as a guiding framework for both individual and societal progress. It further examines the political implications of this ideology, particularly its emphasis on ethical leadership and inclusive nationalism, as well as its influence on contemporary Indian politics. Integral Humanism's relevance persists in addressing modern global challenges, such as economic inequality, environmental degradation, and cultural dislocation. Despite its growing influence in Indian policy, there remains a gap in comparative research, particularly in relation to other postcolonial ideologies. This article suggests further exploration of Integral Humanism's intersections with ideologies like African socialism, Arab nationalism, and Gandhian thought, to enhance its global relevance in the pursuit of alternative development models.